Concurrent Ovarian and Tubal Ectopic Pregnancy After IVF-ET: Case Report and Literature Review - Huang, Yating; Huang, Qin; Liu, Jinglan; Guo, Mengxi; Liu, Yuan; Lai, Dongmei (Frontiers in Physiology, 2022)
Ovarian pregnancy (OP) coupled with tubal ectopic pregnancy is rare. We present a case of coexistent ovarian and tubal ectopic pregnancies in the same adnexa resulting from in vitro fertilization and embryo transfer (IVF-ET) for tubal occlusion. The patient presented with mild vaginal bleeding without abdominal pain. OP was diagnosed via sonographic findings of an ectopic gestational sac (GS) and yolk sac that seemed to be inside her left ovary. Laparoscopic exploration confirmed this diagnosis, and ipsilateral tubal ectopic pregnancy was suspected during surgery. The patient underwent left salpingectomy and resection of the ovarian lesion. A subsequent histopathological examination verified the diagnosis of coexistent ovarian and tubal ectopic pregnancy. Though the mechanism underlying concurrent OP and tubal ectopic pregnancy is still unclear, clinicians should be cautious of potential combined ectopic pregnancy when dealing with patients who have received more than one embryo transfer.